Espículas de esponjas de água doce e fitólitos como indicadores das características paleoambientais desde o Pleistoceno Tardio das ilhas Bandeirantes e Grande, alto rio Paraná. - Rasbold, Giliane Gessica (2016)
The river channel pattern of the upper Paraná River is anabranching type, composed of multi-channel divided by vegetated islands. These islands are important records of environmental and climate events in the last few thousand years (late Pleistocene and Holocene), highlighting the Bandeirantes and Grande Islands. Aiming to understand the formation environments of these islands we analyzed the quantification and qualification of phytoliths and sponge spicules in complement the occurrence of frustules of diatoms, without specific identification. Studies have shown that Bandeirantes island was originated by formation of a ?lake island?, the analyzes of the proxy indicators allowed us to define five formation phases: i) first the central bar formation phase, recorded since the Late Pleistocene (14,620 years cal. BP) with the deposition of Podostemaceae phytoliths type; ii) first transitional phase without the deposition of microfossils; iii) pond phase characterized by the formation of spongofacies composed predominantly by the species Tubella variabilis and Radiospongilla amazonensis, with the preservation of large amounts of frustules, whole diatoms and phytoliths of herbaceous plants; iv) second transitional phase demonstrates that this lake system has undergone gradual clogging since 1220 years cal. BP; v) at least occurs an lowland phase which is characteristic of the current environment. The Grande Island core demonstrates that its formation took place differently than Bandeirantes Island, the scientific literature produced about the study area so far has shown that it was originated through the cut plain. The analysis of phytoliths assemblies, sponge spicules and diatomaceous frustules allowed us the definition of three formation phases: i) central bar phase recorded since 12,425 years cal. BP with the deposition of Podostemaceae phytoliths type; ii) flood plain phase with micropaleontology characteristics refering to the conditions of sediment remobilization; iii) finally levee phase characterized by deposition of phytoliths from grasses and shrubs, associated with sedimentary facies indicative of flood deposits, showing the development of a levee before 2573 years cal. BP as a result of the clipping of the floodplain by channel avulsion.